2003
DOI: 10.1097/01.alc.0000085585.81711.ae
|View full text |Cite
|
Sign up to set email alerts
|

Development and Initial Validation of the Hangover Symptoms Scale: Prevalence and Correlates of Hangover Symptoms in College Students

Abstract: Background: Despite its ubiquity, hangover has received remarkably little systematic attention in alcohol research. This may be due in part to the lack of a standard measure of hangover symptoms that cleanly taps the physiologic and subjective effects commonly experienced the morning after drinking. In the present study, we developed and evaluated a new scale, the Hangover Symptoms Scale (HSS), to potentially fill this void.Methods: Participants were 1230 currently drinking college students (62% women, 91% Cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
154
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(161 citation statements)
references
References 37 publications
7
154
0
Order By: Relevance
“…In terms of cultural aspects, in some societies, alcohol use is considered a demonstration of masculinity, and women are prohibited from consuming alcohol as a sign of submission to men 30 . Physiological differences between men and women were also reported as lower proportional quantities of liquid and higher gastric metabolic rates in women 31 . In terms of age, alcohol use disorders were observed in younger people.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of cultural aspects, in some societies, alcohol use is considered a demonstration of masculinity, and women are prohibited from consuming alcohol as a sign of submission to men 30 . Physiological differences between men and women were also reported as lower proportional quantities of liquid and higher gastric metabolic rates in women 31 . In terms of age, alcohol use disorders were observed in younger people.…”
Section: Discussionmentioning
confidence: 99%
“…In some prior studies, individuals with a family history of alcohol problems have been found to report more frequent hangovers, compared with other drinkers (e.g., Newlin and Pretorius, 1990;Piasecki et al, 2005;Slutske et al, 2003). Low alcohol sensitivity was identifi ed as a risk factor for AUD based on familial high-risk studies; sons of alcoholics were found to display diminished responses to alcohol challenge compared with offspring of nonalcoholics (Schuckit, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Prior analyses of these data established the validity of the morning-report hangover item (Robertson et al, 2012). Specifi cally, hangover was related to the number of drinks consumed the night before, contemporaneous elevations of headache and nausea, and scores on the Hangover Symptoms Scale (Slutske et al, 2003), a retrospective measure of past-year hangover symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…Survey instruments (e.g., Slutske et al, 2003) were not developed for use in acute situations and the items were not necessarily derived from experimental investigations. Some experiments have used items assessing withdrawal rather than hangover (e.g., McCaul et al, 1991;Span & Earlywine, 1999) or hangover symptoms plus cognitive reactions such as guilt (e.g., Span & Earlywine, 1999) or hangover symptoms plus a withdrawal sign invalid for hangover (Kruisselbrink et al, 2006) or gave no information about item selection or validity (e.g., Finnigan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%